FANCM and RECQL genetic variants and breast cancer susceptibility: relevance to South Poland and West Ukraine - Tú Nguyen-Dumont; Aleksander Myszka; Pawel Karpinski; Maria M. Sasiadek; Hayane Akopyan; Fleur Hammet; Helen Tsimiklis; Daniel J. Park; Bernard J. Pope; Ryszard Slezak; Nataliya Kitsera; Aleksandra Siekierzynska; et al. (BMC, 2018)
Abstract Background FANCM and RECQL have recently been reported as breast cancer susceptibility genes and it has been suggested that they should be included on gene panel tests for breast cancer predisposition. However, the clinical value of testing for mutations in RECQL and FANCM remains to be determined. In this study, we have characterised the spectrum of FANCM and RECQL mutations in women affected with breast or ovarian cancer from South-West Poland and West Ukraine. Methods We applied Hi-Plex, an amplicon-based enrichment method for targeted massively parallel sequencing, to screen the coding exons and proximal intron-exon junctions of FANCM and RECQL in germline DNA from unrelated women affected with breast cancer (n = 338) and ovarian cancer (n = 89) from Poland (n = 304) and Ukraine (n = 123). These women were at high-risk of carrying a genetic predisposition to breast and/or ovarian cancer due to a family history and/or early-onset disease. Results Among 427 women screened, we identified one carrier of the FANCM:c.1972C > T nonsense mutation (0.23%), and two carriers of the frameshift insertion FANCM:c.1491dup (0.47%). None of the variants we observed in RECQL were predicted to be loss-of-function mutations by standard variant effect prediction tools. Conclusions Our study of the Polish and Ukrainian populations has identified a carrier frequency of truncating mutations in FANCM consistent with previous reports. Although initial reports suggesting that mutations in RECQL could be associated with increased breast cancer risk included women from Poland and identified the RECQL:c.1667_1667 + 3delAGTA mutation in 0.23-0.35% of breast cancer cases, we did not observe any carriers in our study cohort. Continued screening, both in research and diagnostic settings, will enable the accumulation of data that is needed to establish the clinical utility of including RECQL and FANCM on gene panel tests.